2023
DOI: 10.1038/s41598-023-49197-9
|View full text |Cite
|
Sign up to set email alerts
|

Deployment and assessment of a deep learning model for real-time detection of anal precancer with high frame rate high-resolution microendoscopy

David Brenes,
Alex Kortum,
Jackson Coole
et al.

Abstract: Anal cancer incidence is significantly higher in people living with HIV as HIV increases the oncogenic potential of human papillomavirus. The incidence of anal cancer in the United States has recently increased, with diagnosis and treatment hampered by high loss-to-follow-up rates. Novel methods for the automated, real-time diagnosis of AIN 2+ could enable "see and treat" strategies, reducing loss-to-follow-up rates. A previous retrospective study demonstrated that the accuracy of a high-resolution microendosc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…55 The versatility and compact design of HRME have facilitated its deployment across a spectrum of anatomical sites, spanning from HNC to esophageal squamous cell neoplasia, as well as HPV-associated cervical and anal cancers. [54][55][56][57][58] In 2012, Vila et al demonstrated the feasibility of HRME in the discrimination of benign and malignant mucosa in exvivo HNSCC specimens from 38 patients, achieving a Sn 98.3% and Sp 90.9% with high interobserver reliability. 55 Miles et al then applied HRME to the visual intraoperative margin in 33 HNSCC patients, displaying HRME-generated images to blinded observers.…”
Section: High-resolution Microendoscopymentioning
confidence: 99%
“…55 The versatility and compact design of HRME have facilitated its deployment across a spectrum of anatomical sites, spanning from HNC to esophageal squamous cell neoplasia, as well as HPV-associated cervical and anal cancers. [54][55][56][57][58] In 2012, Vila et al demonstrated the feasibility of HRME in the discrimination of benign and malignant mucosa in exvivo HNSCC specimens from 38 patients, achieving a Sn 98.3% and Sp 90.9% with high interobserver reliability. 55 Miles et al then applied HRME to the visual intraoperative margin in 33 HNSCC patients, displaying HRME-generated images to blinded observers.…”
Section: High-resolution Microendoscopymentioning
confidence: 99%